Maltahöhe - Helmeringhausen (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2020)
526 JPEG files documenting a research trip to farms around Maltahöhe and Helmeringhausen
Keywords: Agricultural laborers; Karakul sheep; Agriculture; Landscapes; Namibia; Karakul Sheep Industry